The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/eji.201444816
|View full text |Cite
|
Sign up to set email alerts
|

Secretory IgA as a vaccine carrier for delivery of HIV antigen to M cells

Abstract: HIV transmission and spread in the host are based on the survival of the virus or infected cells present in mucosal secretions, and the virus' ability to cross the epithelial barrier and access immune target cells, which leads to systemic infection. Therefore, HIV-specific immunity at mucosal sites is critical for control of infection. Although mucosal delivery would ensure the best onset of protective immunity, most candidate vaccines are administered through the parenteral route. Remarkably, secretory IgA (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 21 publications
1
41
0
1
Order By: Relevance
“…Human SIgA were shown to bind to the DC-specific ICAM-3 grabbing nonintegrin (DC-SIGN) and be internalized suggesting that binding to this receptor is a mechanism used by SIgA to prime adaptive immune responses in mucosal tissues (89). This concept was further confirmed by murine studies, which showed that when used as vaccine antigen delivery system, SIgA interacts specifically with M cells present in the GALT or NALT and delivers antigen to mucosal DC for optimal induction of antigen-specific mucosal and systemic immunity (90, 91). …”
Section: Vaccine Adjuvants and Delivery Systems For Induction Of Mmentioning
confidence: 83%
“…Human SIgA were shown to bind to the DC-specific ICAM-3 grabbing nonintegrin (DC-SIGN) and be internalized suggesting that binding to this receptor is a mechanism used by SIgA to prime adaptive immune responses in mucosal tissues (89). This concept was further confirmed by murine studies, which showed that when used as vaccine antigen delivery system, SIgA interacts specifically with M cells present in the GALT or NALT and delivers antigen to mucosal DC for optimal induction of antigen-specific mucosal and systemic immunity (90, 91). …”
Section: Vaccine Adjuvants and Delivery Systems For Induction Of Mmentioning
confidence: 83%
“…Based on the interaction of SIgA with mucosal microfold (M) cells, another study explored the transport of an HIV antigen for immunisation via this mechanism. SIgA bound to the HIV antigen was delivered orally and transported across the epithelial barrier to be captured by dendritic cells, starting mucosal and systemic immune responses that ultimately showed to be protective against infection by a recombinant virus expressing the HIV antigen [203]. Therefore, infection can be impaired by several IgA associated mechanisms, either by immune exclusion, intracellular inactivation, or recognition and activation of the immune system.…”
Section: Iga Mabs In Treating or Preventing Infectionsmentioning
confidence: 99%
“…A trial in Southern Africa demonstrated that HIV‐uninfected women had HIV‐1‐specific IgA antibodies in their vaginal secretions . Interestingly, a recent in vivo study in mice showed the potential of SIgA to serve as a vaccine carrier for a HIV antigen via mucosal administration to target the gastrointestinal environment . In these mice, chemically bound HIV antigen to SIgA was delivered into the intestinal mucosal via oral administration, where SIgA interacted with mucosal microfold cells present in gut‐associated lymphoid tissues.…”
Section: Iga and Fcαri In Mucosal Immunitymentioning
confidence: 99%
“…In these mice, chemically bound HIV antigen to SIgA was delivered into the intestinal mucosal via oral administration, where SIgA interacted with mucosal microfold cells present in gut‐associated lymphoid tissues. These complexes were subsequently selectively captured by dendritic cells and this elicited both humoral and cellular immune responses at systemic and mucosal levels .…”
Section: Iga and Fcαri In Mucosal Immunitymentioning
confidence: 99%